Pengaruh Good Corporate Governance terhadap Tax Avoidance - Nuramal Nuramal; Sitti Mispa; Sahidah Sahidah (AkMen JURNAL ILMIAH, 2023)
The purpose of this study is to determine whether the proportion of independent commissioners, institutional ownership, audit committees and audit quality have effect on the practice of tax avoidance. The research approach used in this study is a quantitative descriptive approach. The population used in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) in 2020 and 2021, namely 50 companies. From the sampling above, the number of samples that met the criteria was 21 companies as a sample, so that the observations for the two periods were 42 (21 x 2). The results of the study found that the Independent Commissioner had a significant positive effect on tax evasion in consumer goods manufacturing companies listed on the Indonesian Stock Exchange (IDX) 2. Institutional ownership had a significant negative effect on tax evasion in consumer goods manufacturing companies listed on the Indonesian Stock Exchange (IDX). Indonesian Stock Exchange (IDX).